Gender Research Ethics Toolkit - CGIAR GENDER Platform (2021)
The toolkit was reviewed by gender researchers, the One CGIAR Ethics Office, and institutional review board members across CGIAR; and updated based on their feedback to make the toolkit a valuable resource during the ethical review of research proposals. The toolkit was presented at a webinar with CGIAR staff on 9 December 2021.